서비스 지향 아키텍쳐 하에서 비즈니스 프로세스 명세에 관한 메타 데이터를 공유하기 위한 온톨로지와 등록저장소의 개발 및 관리 방안 - 김형도(Hyoung-Do Kim); 김종우(Jong-Woo Kim) (한국콘텐츠학회 논문지, 7(11), 2007)
While standardization and its applications for registering and sharing information resources about B2B transactions such as business documents are relatively well developed, it is not easy to register and share business process resources because there are many ways to define complex business processes using different specification(definition) languages. In practice, there are several competing business process specification languages applicable under service-oriented architecture (SOA) such as ebXML BPSS, WS-BPEL, BPMN and so on. A systematic way has to be prepared to register/share diverse and heterogeneous specifications represented using those languages. This paper demonstrates the usefulness of sharing B2B business processes by prototyping a business process registry called ebRR4BP. First of all, we designed a metadata ontology to support the registration of diverse B2B business processes. To implement the proposed metadata ontology using ebXML registries, a mapping scheme to ebXML Registry Information Model is also suggested. The ontology and mapping scheme will be a foundation for supporting common interchange of business process metadata among B2B resistries. 전자문서와 같이 기업간거래에 관한 정보자원의 등록저장 및 공유에 있어서 표준화와 활용은 상당한 진척이 이루어졌으나, 비즈니스 프로세스의 경우 이를 정의하는 방법이 다양하고 복잡한 이유로 비즈니스 프로세스 정보자원의 등록저장 및 공유에는 어려움이 많다. 실제로 ebXML BPSS, WS-BPEL, BPMN 등과 같이 서비스 지향 아키텍쳐 하에서 활용가능한 여러 비즈니스 프로세스 정의 언어들이 시장에서 경쟁하고 있으며, 이들을 이용해서 표현된 다양하고 이질적인 비즈니스 프로세스 명세(정의)들을 체계적으로 등록저장하기 위한 방안이 절실히 필요한 상황이다. 이 논문에서는 ebRR4BP라고 하는 기업간 비즈니스 프로세스 등록저장소 프로토타입을 개발하여, 기업간 비즈니스 프로세스 공유의 유용함을 제시하고자 한다. 이를 위해서 먼저 다양한 기업간 비즈니스 프로세스 등록을 위한 메타데이터 온톨로지를 설계하고, 이를 ebXML 등록저장소에 구현할 수 있도록 ebXML 등록저장소 정보모델로 매핑하는 방안도 구체적으로 제시한다. 이러한 온톨로지와 매핑방안은 기업간거래 등록저장소간의 비즈니스 프로세스 메타데이터의 상호교환을 지원하기 위한 밑바탕이 될 것이다.